Feasibility of Using sCO2 Turbines to Balance Load in Power Grids with a High Deployment of Solar Generation. (15th August 2019) - Bennett, Jeffrey A.; Fuhrman, Jay; Brown, Tyler; Andrews, Nathan; Fittro, Roger; Clarens, Andres F.
Abstract: Solar photovoltaic power generation capacity is growing rapidly, increasing the need for dynamic load balancing when solar production dips. This balancing might be delivered using energy storage and/or advanced power generation cycles, that are compact, dynamic, and highly efficient, such as supercritical carbon dioxide (sCO2 ) cycles. Here, the load balancing capability of a sCO2 combined cycle plant was compared to open cycle and steam combined cycle gas turbines. A characteristic-based transient model was developed to evaluate the impact of machinery ramp rates, minimum part loads, and cycle efficiencies. High resolution demand and solar irradiance data from the University of Virginia campus, before and after installation of a major solar project, was used to represent low and high levels of solar deployment in the grid. The results suggest that under high deployment of solar power, sCO2 cycles and steam combined cycle systems with ramp rates greater than 5.75%/minute can balance load and provide comparable levelized costs of electricity (0.057/kWh). Solar curtailment was driven by the minimum part load capabilities. A sCO2 cycle with a minimum part load of 30% was predicted to have a curtailment of 15% in the high solar scenario without a battery, and 4% with a 30 MWh battery.